Successful utilization of the EMR in a multiple sclerosis clinic to support quality improvement and research initiatives at the point of care. Issue 4 (November 2018) - Claire Simon, Kelly; Hentati, Afif; Rubin, Susan; Franada, Tiffani; Maurer, Darryck; Hillman, Laura; Tideman, Samuel; Szela, Monika; Meyers, Steven; Frigerio, Roberta; Maraganore, Demetrius M
Background: Many physicians enter data into the electronic medical record (EMR) as unstructured free text and not as discrete data, making it challenging to use for quality improvement or research initiatives. Objectives: The objective of this research paper was to develop and implement a structured clinical documentation support (SCDS) toolkit within the EMR to facilitate quality initiatives and practice-based research in a multiple sclerosis (MS) practice. Methods: We built customized EMR toolkits to capture standardized data at office visits. Content was determined through physician consensus on necessary elements to support best practices in treating patients with demyelinating disorders. We also developed CDS tools and best practice advisories within the toolkits to alert physicians when a quality improvement opportunity exists, including enrollment into our DNA biobanking study at the point of care. Results: We have used the toolkit to evaluate 541 MS patients in our clinic and begun collecting longitudinal data on patients who return for annual visits. We provide a description and example screenshots of our toolkits, and a brief description of our cohort to date. Conclusions: The EMR can be effectively structured to standardize MS clinic office visits, capture data, and support quality improvement and practice-based research initiatives at the point of care.